The Transition of Pre-service Chemistry Teachers' Concept Mastery about Solutions in Multiple Representations-Based Learning - Muhamad Imaduddin; Sri Haryani (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Indraprasta PGRI, 2019)
The purpose was to analyze the transition of pre-service chemistry teachers' concept mastery about solutions in multiple representations-based learning. This research was set through pre-experimental design which is one-group pretest-posttest design. Multiple representations-based learning was applied to Basic Chemistry II course involving 31 first-year pre-service chemistry teachers. The instruments were a self-assessment sheet on the ability to connect multiple levels of representation (PD-MLP) and the concept mastery tests about solutions (TPKL). Self-assessment and concept mastery was measured based on the scores of the pre-test and post-test and analyzed through normalized gain calculations. Mastery of the concept consists of five mastery indicators. The gain of the concept mastery is at a moderate level (0.30) entirely. Mastery of concept I and IV are much lower than the mastery of other concepts. The shifting groups from TMK category (Not Mastering the Concept) to MSKK (Mastering a Small Part of the Concept) are the most group of pre-service teachers. There is a pre-service teacher who has changed the category from TMK to MK (Mastering the Concept). This pattern can be understood by reviewing the process of concept formation and memory workspace. The instructional content is able to reduce the barrier of feeling difficult. This can be seen from the results of the teachers’ self-assessment of their ability to connect the level of chemical representations leading to a positive direction. This indicates that conceptual understanding increases. The transition of pre-service chemistry teachers’ concept mastery is heading towards a better direction after experiencing multiple representations based-learning.